2005
DOI: 10.1177/1356336x05052893
|View full text |Cite
|
Sign up to set email alerts
|

Character, virtue and physical education

Abstract: In this article I argue that until the full complexity of the psychology of moral personality, moral action, and moral learning is recognized, the prospect of physical education, and team sports in particular, being utilized for moral and social development is slim. Similarly a recognition of the multifarious, heterogeneous and context specific account of moral goodness must also be embraced. Once we move away from the dominant reductive account of moral action and moral goodness, a more realistic and appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
30

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 26 publications
0
42
0
30
Order By: Relevance
“…As a subject which has a long history of legitimising itself on the grounds of its contribution to pupils' social and moral welfare (Arnold 1980;Jones 2005Jones , 2008Hargreaves 1986;Hellinson et al 1995;Hellinson & Martinek 2006;Loland 2006;Siedentop 1994), it would seem reasonable to assume that actors within Physical Education Teacher Education (PETE) might embrace recent cries for the need to re-moralise society due to the conditions of the late modern age (Giddens 1991), and not least the pleas for professional teachers to perceive their role within moral, as opposed to technical terms (Cochran-Smith 2005;Hargreaves 2003;Laker 2000;Sachs 2001). In this article we will, however, make the case that this very legacy of moral development through the physical can paradoxically be seen to do considerable 'ideological work' (Hall 1985, cited in Kirk 1992 which hampers the nurturing of inclusive, local learning environments which celebrate and respect diversity of citizens in a democratic, late-modern society.…”
Section: Introductionmentioning
confidence: 99%
“…As a subject which has a long history of legitimising itself on the grounds of its contribution to pupils' social and moral welfare (Arnold 1980;Jones 2005Jones , 2008Hargreaves 1986;Hellinson et al 1995;Hellinson & Martinek 2006;Loland 2006;Siedentop 1994), it would seem reasonable to assume that actors within Physical Education Teacher Education (PETE) might embrace recent cries for the need to re-moralise society due to the conditions of the late modern age (Giddens 1991), and not least the pleas for professional teachers to perceive their role within moral, as opposed to technical terms (Cochran-Smith 2005;Hargreaves 2003;Laker 2000;Sachs 2001). In this article we will, however, make the case that this very legacy of moral development through the physical can paradoxically be seen to do considerable 'ideological work' (Hall 1985, cited in Kirk 1992 which hampers the nurturing of inclusive, local learning environments which celebrate and respect diversity of citizens in a democratic, late-modern society.…”
Section: Introductionmentioning
confidence: 99%
“…Angyal et al (2003), in a study related to the typical adolescent problem of compatibility, found that during a variety of artistic activities a process of compliance began to develop between adolescents and their families and peers. The results of research by Jones (2005) showed that physical education lessons affected character development. Additionally it appears that middle school physical education and sports activities contribute to behavior appropriate to societal values, culture and morals, as well as compliant behavior in social environments (Akıncı, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Attention to how one negotiates these competing discourses could form an important part of an alternative Olympic pedagogy. Importantly, this would not be done by adhering to a traditional view of learning through sport where learning is seen to take place by default (Jones 2005;Theodoulides and Armour 2001). Rather, learning (and coaching) could take place in a reflective manner with attention to the cultural dimensions of settings (Kirk and Kinchin 2003) and the role of significant others (Lave and Wenger 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Although sport's educational capacity in the socio-moral realm has received attention (see Jones 2005, Theodoulides 2003, Theodoulides and Armour 2001, for thoughtful discussions), consensus on whether and how it might be realised has not been forthcoming. With specific reference to Olympism, a handful of theorists have examined teaching and learning in schools (Binder 2001;Kohe 2010), but few authors have considered how participants might experience the philosophy.…”
Section: Learning the Olympic Waymentioning
confidence: 99%